Tumor Marker Decline in Predicting Treatment Outcome among Poor-Risk Testicular Germ Cell Tumors—A Tertiary Cancer Center Data - K., Lakshmi Haridas; James, Francis V.; Kumar, Aswin; Joseph, John; KM, Jagathnath Krishna (South Asian Journal of Cancer, 2022)
Introduction Testicular germ cell tumors are rare in India. Despite the advances in chemotherapy, poor-risk testicular nonseminomatous germ cell tumors (NSGCT) remain as a clinical challenge. Various prognostic factors have been described in this rare disease. The Indian data in this regard is scarce. Our study is the first attempt to assess the tumor marker decline with respect to treatment outcome in poor-risk NSGCT in Indian patients.Materials and Methods This retrospective study was done among newly diagnosed poor-risk NSGCT, treated at genitourinary clinic, at our tertiary cancer center during the period 2017 to 2019. The prognostic significance of tumor marker decline in them was correlated with 2-year progression-free survival (PFS) and 2-year overall survival (OS).Statistical Methods The association between two variables were assessed using chi-squared/Fischer's exact test. The PFS and OS were estimated using Kaplan–Meier method and the significance difference between survival curves was tested using log rank test. The risk for survival was estimated using cox regression analysis. A p-value of <0.05 was considered as significant.Results Out of 11 eligible patients, four (36%) had favorable tumor marker decline and seven (64%) had unfavorable decline. The 2-year PFS among favorable and unfavorable decline group were 66.7 and 42.9%, respectively (p-0.358), and the 2-year OS was 66.7 and 71.4%, respectively (p-0.974). Teratoma was not found to be a significant factor in our study. Tumors with only beta human chorionic gonadotropin (βHCG) elevation were observed to have good outcome. Postchemotherapy unresectable residual disease showed a significant trend toward inferior survival, the 2-year PFS was 38 versus 100% (p-0.188) and the 2-year OS was 62.5 versus 100% (p-0.334) in patients with and without unresectable residual disease, respectively.Conclusion Majority of our poor-risk NSGCT patients had unfavorable tumor marker decline and progressive events. However, the survival difference was not significant, given the small sample size. Tumors with only βHCG elevation were observed to have good outcome. Postchemotherapy unresectable residual disease showed a significant trend toward inferior survival.
Keywords: poor risk NSGCT; tumor marker decline; postchemotherapy residual disease; chemointensification; nonseminomatous germ cell tumors